Are nonclinical obsessive-compulsive symptoms associated with bias toward habits?. (30th July 2016) - Snorrason, Ivar; Lee, Han Joo; de Wit, Sanne; Woods, Douglas W.
Abstract: In a sample of student volunteers ( N =93), we found that obsessive-compulsive symptoms (although not hoarding) were associated with overreliance on stimulus-response habits at the expense of goal-directed control during instrumental responding. Only checking symptoms were associated with bias toward habits after negative affect was controlled for. Further research is warranted to examine if overreliance on habits represents an aberrant learning process that confers risk for obsessive-compulsive psychopathology. Highlights: We examined habit learning and self-reported OC symptoms among student volunteers. Bias toward habits was associated with all OC symptom dimensions except hoarding. After controlling for negative affect, checking symptoms were associated with bias toward habits.